WATER PURIFICATION BY ADSORPTION CAPACITY OF CRYSTAL VIOLET DYE ON RAW AND MODIFIED AZADIRACHTA INDICA BIOMASS (Journal of Medical & Health Sciences Review, 2025)
Green chemistry brought an additional focus to environmental security. Additionally, since dye contamination in aquatic systems has developed into a significant environmental issue, green synthetic plant-based adsorbents for the dye degradation have also garnered considerable attention. In detection of green research, common neem (Azadirachta indica) leaves has been used as an adsorbent to study its adsorption capacity on crystal violet dye. At various adsorbent dosages, adsorption times, dye concentrations, and pH levels of the solution, the ability of the adsorbent to adsorb CV dye was assessed. Batch adsorption studies were used to demonstrate the adsorbent's removal effectiveness for CV. Catalytic activity of the synthesized adsorbents was studied using CV dye, showing rapid degradation of CV in the first 90 min using raw neem biomass and after modifications with sulfanilamide and malonic acid its optimized time decreases to 60 min. The efficiency of adsorbent to remove CV dye was 90% with relatively low amount of biomass i.e., 0.15 g using raw neem leaves. 0.1 g using AI modified with sulfanilamide and 0.08 g using AI modified with malonic acid. Studies showed that it has best adsorption capacity at high pH value. After optimized value of contact time, initial dye concentration, dose, and pH, further increase in dose, time or concentration decreases the adsorption rate as the active sites available by the adsorbent for dye molecule becomes filled. Studies also revealed that after modification of neem leaves with sulfanilamide and malonic acid, its adsorption capacity increases and sulfanilamide modification gives best results.  All this reveals that neem leaves can be used as alternates of costly adsorbents for the CV dye removal from textile waste water and have high better adsorption capacity.